2012
DOI: 10.1136/bmjspcare-2012-000265
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate My Care: a clinical service that coordinates care, giving patients choice and improving quality of life

Abstract: The CMC service has a well defined pathway underpinned by an electronic solution. It has been shown to change culture and deliver fully integrated, personalised end of life care. A pan-London CMC roll out will take place over the next 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 9 publications
1
43
0
1
Order By: Relevance
“…Many of the hospital clinicians in our case study and peer review group, and some primary care professionals, said the surprise question was of limited value if they did not know the patient well, or if the patient was at risk of dying but currently more stable. Our collaborative approach has led to continuing partnerships with projects using the SPICT to identify patients in primary and secondary care settings 7 27…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the hospital clinicians in our case study and peer review group, and some primary care professionals, said the surprise question was of limited value if they did not know the patient well, or if the patient was at risk of dying but currently more stable. Our collaborative approach has led to continuing partnerships with projects using the SPICT to identify patients in primary and secondary care settings 7 27…”
Section: Resultsmentioning
confidence: 99%
“…Simple identification tools based on accepted clinical indicators, such as SPICT, are needed to support this change in practice. Better identification, holistic assessment and anticipatory care planning for future deterioration, could help to reduce the substantial risk of unplanned hospital admissions and prolonged inpatient stays experienced by all the patients we identified 21 27 28. Primary care teams have previously indicated that they would welcome guidance from hospital specialists about when to put patients on their palliative care registers or open discussions about future care goals 5 25 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral discussions are not always formally recorded in writing. Uniform use of the same approach including how and where this information is held and facilitating access to other health professionals suggests this could lead to a reduction in avoidable hospital admissions and greater satisfaction 14 15…”
Section: Discussionmentioning
confidence: 99%
“…In the community, health professionals from primary care, the voluntary sector, the ambulance service and hospital teams may be involved in the care of an individual, and access to dynamic care plans which enable changes in preferences to be recorded need to be used uniformly. Success of such measures has been reported in other parts of the UK 15. Currently preferences expressed are recorded in the community hospice notes, recorded on the shared palliative/oncology systems database, conveyed verbally, discussed in primary care meetings (where these occur) and are passed onto the GP out of hours service.…”
Section: Discussionmentioning
confidence: 99%